MULTIFUNCTIONAL TEACHER: A STATE-OF-THE-ART STUDY ON ACADEMIC PRODUCTIONS (1997-2017) - Machado Lima, Vanda Moreira [UNESP]; Ponce, Rosiane de Fatima [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
This paper aims to present the results of a research that investigated academic productions in the area of education in the period from 1997 to 2017 on the teacher who works in the initial years of elementary school (AIEF) and teaches in public schools. The research carried out was of the State of the Art type from three central sources: theses and dissertations, articles in journals and works in events. A total of 7,497 productions were surveyed within the theme, of which 67 were analyzed by pre-defined criteria. In general, the surveyed productions prioritized the global performance of this professional without emphasis on a discipline or on special content. Most of these productions were developed in public institutions and most of the authors were female (88%). The choice for the qualitative approach was predominant with empirical studies counting on the professor as the participant subject of the research. There was the use of various instruments in the production/collection of data, mainly the use of interviews and questionnaires, followed by documentary analysis and observations. We concluded, from the analyzed researches, that the study about the polyvalent professional teacher that acts in the AIEF in the public school and emphasizes questions about his initial and continued formation stands out.
Keywords: Multifunctional teacher; State of the art; Early years of elementary school; Public school